2021
DOI: 10.3390/horticulturae7080223
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Application Methods of Boron on Tomato Growth, Fruit Quality and Flavor

Abstract: The effect of application methods with different boron levels on the growth, fruit quality and flavor of tomato (Solanum lycopersicum L., cv. ‘Jinpeng No.1’) were investigated under greenhouse conditions. Seven treatments used included two application methods (leaf and root application) with four boron levels (0, 1.9, 3.8 and 5.7 mg∙L−1 H3BO3). Experimental outcomes revealed that both application methods significantly increased net photosynthetic rate and chlorophyll content, and stabilized leaf structure of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
10
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(13 citation statements)
references
References 50 publications
2
10
1
Order By: Relevance
“…Meanwhile, for boron application, Treatment 6 was significantly difference compared to Treatment 2. These findings contrasted with the study by Xu et al (2021), who discovered that boron treatments had a substantial impact on tomato plant biomass accumulation. The fresh weight and dry weight of shoots were both enhanced by boron treatment to the leaves and the roots, however the root application produced larger root and shoot dry weight ratios than the leaf application did.…”
Section: Shoot Biomasscontrasting
confidence: 99%
See 1 more Smart Citation
“…Meanwhile, for boron application, Treatment 6 was significantly difference compared to Treatment 2. These findings contrasted with the study by Xu et al (2021), who discovered that boron treatments had a substantial impact on tomato plant biomass accumulation. The fresh weight and dry weight of shoots were both enhanced by boron treatment to the leaves and the roots, however the root application produced larger root and shoot dry weight ratios than the leaf application did.…”
Section: Shoot Biomasscontrasting
confidence: 99%
“…Treatment T3, T5 and T7 showed the significant effects compared to other treatments. These results are similar according to Xu et al (2021), who demonstrated that boron may stabilize leaf structure and successfully stimulate the synthesis of photosynthetic pigments, which directly improve tomato plants' ability to photosynthesize. For boron application, result showed there were significant differences of plant number of leaves among the treatments especially for treatment T4, T6, T8 and T16.…”
Section: Plant Number Of Leavessupporting
confidence: 87%
“…26 In addition, an interconnection between B and Ca exists because B increases the Ca absorption in fruit. 27 This might be the explanation according to which Ca and B content simultaneously occurred as differentiation markers in the geographical discrimination models.…”
Section: Resultsmentioning
confidence: 97%
“…Best results in all parameters assessed were noticed at B concentration of 1.80mg.L -1 meaning that this concentration adds to the existing 0.15ppmoptimizes vegetative and reproductive growth of tomato. In a related study 18 found foliar application of Boron at concentration of 1.9mgL -1 to optimize plant growth and photosynthetic indices in tomato. This could be attributed to the involvement of boron in both structural and functional physiological biochemistry in plant development.…”
Section: Resultsmentioning
confidence: 99%
“…From a physiological point of view, boron application increase chlorophyll a, b and carotenoids content in tomato leaves more than twice compared to same crop grown under boron deficient substrate, hence boron appreciably increase net photosynthetic rate. 18…”
Section: Resultsmentioning
confidence: 99%